Demographic and disease‐related factors impact on cerebrospinal fluid neurofilament light chain levels in multiple sclerosis. Issue 1 (27th December 2022) - Zondra Revendova, Kamila; Starvaggi Cucuzza, Chiara; Manouchehrinia, Ali; Khademi, Mohsen; Bar, Michal; Leppert, David; Sandberg, Elisabeth; Ouellette, Russell; Granberg, Tobias; Piehl, Fredrik
Abstract: Background: Neurofilament light (NfL) levels reflect inflammatory disease activity in multiple sclerosis (MS), but it is less clear if NfL also can serve as a biomarker for MS progression in treated patients without relapses and focal lesion accrual. In addition, it has not been well established if clinically effective treatment re‐establishes an age and sex pattern for cerebrospinal fluid NfL (cNfL) as seen in controls, and to what degree levels are affected by disability level and magnetic resonance imaging (MRI) atrophy metrics. Methods: We included subjects for whom cNfL levels had been determined as per clinical routine or in clinical research, classified as healthy controls (HCs, n = 89), MS‐free disease controls (DCs, n = 251), untreated MS patients (uMS; n = 296), relapse‐free treated MS patients (tMS; n = 78), and ProTEct‐MS clinical trial participants (pMS; n = 41). Results: Using linear regression, we found a positive association between cNfL and age, as well as lower concentrations among women, in all groups, except for uMS patients. In contrast, disability level in the entire MS cohort, or T1 and T2 lesion volumes, brain parenchymal fraction, thalamic fraction, and cortical thickness in the pMS trial cohort, did not correlate with cNfL concentrations. Furthermore, the cNfL levels in tMS and pMS groups did not differ. Conclusions: In participants with MS lacking signs of inflammatory disease activity, disease modulatory therapy reinstates an age and sex cNfL pattern similar to that of control subjects. No significant association was found between cNfL levels and clinical worsening, disability level, or MRI metrics. Abstract :